A Comparison of Perceived and Observed Learning From Professional Development: Relationships Among Self-Reports, Direct Assessments, and Teacher Characteristics. (March 2021) - Copur-Gencturk, Yasemin; Thacker, Ian
The success of professional development programs has typically been determined based on their impact on teacher learning, without much attention being given to the data sources used. Large-scale studies have generally relied on teachers' self-reports, whereas small-scale studies have included more direct assessments and observations of teacher learning. The purpose of this study was to compare teachers' self-reported gains in mathematical knowledge for teaching with those measured by direct assessments. Quantitative analyses of the data collected from 545 teachers who participated in content-focused professional development programs indicated a lack of correlation between teachers' self-reports and direct assessments of their knowledge gains. Furthermore, different teacher-related factors were associated with the learning reported by these two measures. These findings speak to the need to pay careful attention to the outcome measures used to evaluate teachers' learning.